The review of Rice Potential Production on Sungai Ular Irrigation Fields in Perbaungan District Serdang Bedagai Regency - Ade Rina Manik; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2015)
Serdang Bedagai as one of rice centra in North Sumatera need to be reviewed its irrigation network to hold out and increase production. The purpose of this research was to study the rice potential production on Sungai Ular irrigation fields in Perbaungan district Serdang Bedagai regency in achieving the maximum level of rice production based on sun radiation level, time to grow rice, and rice variety. The research also studied the ratio between irrigation field and crops field, the ratio between technical irrigation with pre technical and conventional irrigation and also realibility of existing irrigation network. In the year of 2009-2013, the results indicated that the irrigation network realibility was need to increase. The average ratio between irrigation field and crops field was 1,80, the average ratio between technical irrigation with pre technical irrigation and conventional irrigation was 0,57 and the rice production target was 58,89 %. Keywords: irrigation network. potential production, production target, rice